Environmental Configuration and Innovation: Different Impacts in the Measurement of the Innovative Process in Brazil and in its States - Gutemberg Ribeiro; Ana Paula Mussi Szabo Cherobim (BBR: Brazilian Business Review)
This article aims to demonstrate that environmental variables can assume differentiated values over a given period and associate themselves to form configurations of different contexts. Knowing the possible configurations of the organizational environment, we are able to identify which indicators are most appropriate to measure innovation, thus meeting the basic condition to manage innovation: to measure accurately the phenomenon under analysis. Thus, with the empirical data analysis from Brazil and the states of São Paulo, Paraná and Sergipe, we are able to highlight and characterize the different environmental configurations and their reflexes for the innovation measurement process. It should be emphasized that the environmental configuration appears as a relevant factor that must be considered in the process of measurement and management of innovation aiming at competitiveness.